Evaluation of the application value of a three-dimensional digital model of the knee in clinical practice - Keremu, Ajimu; Mijiti, Nuersimanguli; Mijiti, Sirejiding; Tuxun, Aikebaier; Abudurexiti, Abulikemu (Journal of international medical research, 2020)
Objective To compare the knee shape and bone parameters between knee prosthesis products from overseas companies and a Chinese patient’s knee, and to apply the anatomical basis for Chinese knee prosthesis design. Methods Three-dimensional digital models were built, including prosthesis products for a normal adult. The relevant anatomy index was measured, and physical parameter, radiographic, geometric, knee kinematic, and distal geometry data were collected on the femur and tibia. Results The width of the femoral condyle (WFC), width of the medial femoral condyle (WMFC), width of the lateral femoral condyle (WLFC), depth of the intercondylar fossa (DICF), sagittal length of the medial femoral condyle (SLMFC), sagittal length of the lateral femoral condyle (SLLFC), angle of the medial femoral condyle (AMFC), and angle of the lateral femoral condyle (ALFC) in the femur and the transverse diameter (ML) and anteroposterior diameter (AP) of the tibial bone were measured. These parameters were significantly lower in the normal group compared with the prosthesis product model group. Conclusion When using an imported knee prosthesis, the osteotomy angle may not fit perfectly. Use of an imported prosthesis may be an important factor in the increasing failure of knee arthroplasty in China.